Sub-surface characterisation of latest-generation identification documents using optical coherence tomography. Issue 2 (March 2021) - Marques, Manuel J.; Green, Robert; King, Roberto; Clement, Simon; Hallett, Peter; Podoleanu, Adrian
Highlights: Need to distinguish legitimate from counterfeit documents. High-throughput, sensitive, high-resolution imaging methods required. Modern documents present sub-surface security features. Optical coherence tomography (OCT) allows sub-surface, non-destructive imaging. OCT was used here to image security features embedded in questioned documents. Abstract: The identification of individuals, particularly at international border crossings, coupled with the evolving sophistication of identity documents are issues that authorities must contend with. Particularly, the ability to distinguish legitimate from counterfeit documents, with high throughput, sensitivity, and selectivity is an ever-evolving challenge. Over the last decade, an increasing number of security features have been introduced by authorities in identification documents. The latest generation of travel documents (such as passports and national ID cards) forego paper substrates for several layers of polycarbonate, allowing security features to be embedded within the documents. These security features may contain information at either the superficial and sub-surface levels, thus increasing the document's resilience to counterfeiting. As the documents become harder to forge, so does the sophistication of forgery detection. There appears to be an unmet and evolving need to identify such sophisticated forgeries, in a non-destructive, high throughput manner. In this publication, we report on the application of optical coherence tomography (OCT) imaging on assessing security features in specimen passports and national ID cards. OCT allows sub-surface imaging of translucent structures, non-destructively enabling quantitative visualisation of embedded security features.